2010
DOI: 10.2478/v10134-010-0044-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute adaptive responses of central sensorimotor neurons after spinal cord injury

Abstract: Spinal cord injury (SCI) can be a lifelong, devastating condition for both the patient and the caregiver, with a daunting incidence rate. Still, there are only limited available therapies and the effectiveness of precise regeneration within the central nervous system is minimal throughout postnatal life. Recently, improved regeneration after SCI was seen by manipulating a pathway in sensorimotor neocortices that is involved in phosphorylation of an RNA binding protein (RBP) required for mRNA translation, the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Finally, acute traumas can alter functions of distinct regulatory members of mRNA translation. For example spinal cord injury alters mRNA binding signature of EIF4E in neocortical neurons contralateral to the hemisection model (Thompson K, 2010), an initiation factor that in our screen came as part of GO:RNA binding. These data suggest that post-spinal cord injury mRNAs for possible regenerative efforts are acutely present in central neurons, but their translation is disrupted.…”
Section: Discussion and Implications For Future Studiesmentioning
confidence: 99%
“…Finally, acute traumas can alter functions of distinct regulatory members of mRNA translation. For example spinal cord injury alters mRNA binding signature of EIF4E in neocortical neurons contralateral to the hemisection model (Thompson K, 2010), an initiation factor that in our screen came as part of GO:RNA binding. These data suggest that post-spinal cord injury mRNAs for possible regenerative efforts are acutely present in central neurons, but their translation is disrupted.…”
Section: Discussion and Implications For Future Studiesmentioning
confidence: 99%
“…R ecent studies in spinal cord injury (SCI) have shown that remote regenerative responses in the brain could be induced after SCI, [1][2][3][4][5][6][7][8] as could local responses in the injured spinal cord. [9][10][11] Brain network reorganization is critical for functional recovery after SCI in both nonhuman primate SCI models 12,13 and clinical patients with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression profiling in the brain post-SCI has shown that acute adaptive regenerative responses in the brain were induced after SCI, 1 and that the SCI-induced molecular pathways in the brain may play an important role in recovery from the injury. [1][2][3] However, as gene expression profiling in the brain after intravenous infusion of MSCs post-SCI has not yet been assessed, in this study, genome-wide RNA profiling in the motor cortex was performed following intravenous infusion of MSCs post-SCI induction in a rat model of contused SCI. Moreover, the gene expression signature in the brain that might be associated with the functional improvements induced by the infused MSCs after SCI was explored.…”
Section: Introductionmentioning
confidence: 99%